Profile of the Exporting Company or with Exporting Potencial in Costa Rica - López Peña, kendall Ariana (2017)
The International System of the XXI century, characterized by a high economic and digital globalization, generate the need for companies to know their work environment, which from a technical point of view, Competence and other basic elements of a market study. This article corresponds to the results of the Descriptive Research carried out for the Basic Market Study in the Sector of Foreign Trade Services and Internationalization of PYMES in Costa Rica.